Software Developers' Views of End-Users and Project Success. - PROCACCINO, J. DREW; VERNER, JUNE M. (Communications of the ACM, 2009)
The article discusses software development project management. The authors compare and contrast perceptions held by software developers and end-users regarding the successful attributes, functions, and requirements of systems made for end-users. Software development has been challenged by projects that were developed over-budget, late, and with limited functionality, the authors state. Other topics of discussion include ineffective communication between systems developers and end-users and what end-users consider to be important in the developmental process.